Leniency, Asymmetric Punishment and Corruption: Evidence from China - Maria Perrotta Berlin; Giancarlo Spagnolo; Bei Qin (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2017)
Leniency policies and asymmetric punishment are regarded as potentially powerful anticorruption tools, also in the light of their success in busting price-fixing cartels. It has been argued, however, that the introduction of these policies in China in 1997 has not helped fighting corruption. Following up on this view, the Central Committee of the Chinese Communist Party passed, in November 2015, a reform introducing heavier penalties, but also restrictions to leniency. Properly designing and correctly evaluating these policies is difficult. Corruption is only observed if detected, and an increase in convictions is consistent with both reduced deterrence or improved detection. We map the evolution of the Chinese anti-corruption legislation, collect data on corruption cases for the period 1986-2010, and apply a new method to identify deterrence effects from changes in detected cases developed for cartels by Miller (2009). We document a large and stable fall in corruption cases starting immediately after the 1997 reform, consistent with a negative effect of the reform on corruption detection, but under specific assumptions also with increased deterrence. To resolve this ambiguity, we collect and analyze a random sample of case files from corruption trials. Results point to a negative effect of the 1997 reform, linked to the increased leniency also for bribe-takers cooperating after being denounced. This likely enhanced their ability to retaliate against reporting bribe-givers – chilling detection through whistleblowing – as predicted by theories on how these programs should (not) be designed.
Keywords: K14; N45; P37; 330; Corruption; Leniency; Deterrence; China